2020
DOI: 10.1017/s0007114520001774
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation withLactobacillus plantarummodified gut microbiota, bile acid profile and glucose homoeostasis in weaning piglets

Abstract: Bile acids (BA) have emerged as signalling molecules regulating intestinal physiology. The importance of intestinal microbiota in production of secondary BA, for example, lithocholic acid (LCA) which impairs enterocyte proliferation and permeability, triggered us to determine the effects of oral probiotics on intestinal BA metabolism. Piglets were weaned at 28 d of age and allocated into control (CON, n 14) or probiotic (PRO, n 14) group fed 50 mg of Lactobacillus plantarum daily, and gut microbiota and BA pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…Feeding the Lactobacillus amylovorus strain, which is dominant in the pre-weaning pig microbial community, could help in maintaining its presence in post-feeding and contributing to protecting the post-weaning piglets from E. coli F4 infection [46]. In agreement with Konstantinov et al [46], another lactic acid bacteria (LAB), Lactobacillus plantarum, has shown promising results, contributing to increasing the level of recognized beneficial bacteria, including bacteria belonging to the Bifidobacteriaceae family [124] and the genera Lactobacillus and Mitsuokella [125,126]. More recently, attention to other bacteria, in addition to LAB bacteria, has increased and, of them, Bacillus spp.…”
Section: Post-weaning Dietmentioning
confidence: 71%
“…Feeding the Lactobacillus amylovorus strain, which is dominant in the pre-weaning pig microbial community, could help in maintaining its presence in post-feeding and contributing to protecting the post-weaning piglets from E. coli F4 infection [46]. In agreement with Konstantinov et al [46], another lactic acid bacteria (LAB), Lactobacillus plantarum, has shown promising results, contributing to increasing the level of recognized beneficial bacteria, including bacteria belonging to the Bifidobacteriaceae family [124] and the genera Lactobacillus and Mitsuokella [125,126]. More recently, attention to other bacteria, in addition to LAB bacteria, has increased and, of them, Bacillus spp.…”
Section: Post-weaning Dietmentioning
confidence: 71%
“…The FXR is a key target of bile acid metabolism and is involved in lipid metabolism regulation. Intestinal FXR regulates liver CYP7A1 by acting on the fibroblast growth factor 15 (FGF15) and improves bile acid metabolism [38,39]. Our previous study found that probiotic Bif.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the wide-ranging and important functions of BAs, BA pro le analysis is garnering increasing attention in medicine and zootechnics (Fu et al 2020;Lin et al 2020). However, neither the reason for nor the effect of changes in BA pro les has received su cient attention in sh.…”
Section: Discussionmentioning
confidence: 99%
“…Even a slight difference in BA hydroxylation patterns may exert drastically different biological responses (Li and Chiang 2009;Song et al, 2015). Therefore, BA pro le assessments are garnering increasing interest to screen potential biomarkers for the early diagnosis of human liver and intestinal diseases (Fu et al 2020;Slopianka et al 2017), malnutrition (Lin et al 2020), and healing processes (Roda et al 2019). It was noticed that the BA pro les of sh could be in uenced by diet (Zhang et al 2017), however, it was unclear about the agent in diet that exerted the effect.…”
Section: Introductionmentioning
confidence: 99%